Implementasi Kode Etik Pustakawan di Perpustakaan Umum Daerah Kabupaten Tanah Datar - Antika, Dini; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
Abstract The purpose of writing this paper is (1) Describe how the librarian's code of ethics is implemented in the Tanah Datar District Public Library; (2) Knowing the relationship between librarians and visitors in the Tanah Datar District Public Library; (3) Describe the relationship between librarians and fellow librarians in the Tanah Datar District Public Library; (4) Knowing the relationship between librarians and their service to libraries in the Tanah Datar District Public Library; (5) Knowing the relationship between librarians working in the Tanah Datar District Public Library and professional organizations; (6) Describe the relationship of librarians working in the Tanah Datar District Public Library with the community in the library. Writing this paper uses descriptive research methods. Data is collected based on interviews with librarians and visitors. Based on the results of the study it can be concluded as follows. First in achieving excellence librarians participate in activities in the library field. Librarians consider decisions professionally by choosing activities about library science. The advantage gained by librarians in serving users is inner satisfaction, lots of acquaintances and motivation to read. Second, librarians serve visitors who come to the library fairly. Scientific works can only be read in the library. Third, librarians achieve excellence in the profession by attending library science training. In establishing relationships with colleagues in the library, a small number of librarians have not been able to establish good relationships with colleagues in the library and question the differences that occur. Fourth, librarians attend training whose knowledge can be utilized for library development. Librarians collaborate with reading parks, and all types of libraries. Fifth, librarians never pay any fees in the library because the activities to be carried out at the library are funded by the local government. Most librarians can distinguish between personal life views and professional needs. Sixth, librarians work with communities in library fields such as literacy tree houses and reading parks established by students. Librarians contribute to the development of culture in the community in the form of a mobile library that can be utilized by the community.Keywords: implementation; librarians; code of ethics.